Optimal PV Placement to Reduce Power Loss and Improve Voltage in Distribution Network System Using K-means Clustering Method - Syukri Yunus; Melda Latif; Darwison Darwison (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2022)
Placing the PV in the right location will maintain the utility voltage, but if the placement of PV in the wrong location will cause the stability of the system to be affected. In this study, optimization of PV placement uses the K-means Clustering method. This method will group each node in the system from the point of view of operating characteristics LSF (loss sensitivity factor) and dV (voltage deviation). The results of grouping each bus with the K-means Clustering method will be the basis for determining the location of PV placement in the IEEE 37 and 69 bus distribution systems. In this method, grouping results are used based on the size of the proximity and have the same characteristics with each other. In determining the optimal location for PV placement, the addition of PV will reduce power losses and improve voltage. Optimal PV location placement in the IEEE 37 bus distribution system is placed on 3 buses with a power capacity of 60% where the value of power losses drops to 176.2 kW and the voltage profile is the best but there are some buses that are still under voltage and overvoltage. Meanwhile, the most optimal PV location for the IEEE 69 bus distribution system is placed on a 6 bus with a power capacity of 60% where the value of power losses drops to 149.5 kW and the voltage profile of each bus is in normal condition..